Healthy broilers disseminate antibiotic resistance in response to tetracycline input in feed concentrates. (December 2020) - Sreejith, S.; Shajahan, Shamna; Prathiush, P.R.; Anjana, V.M.; Viswanathan, Arathy; Chandran, Vishnu; Ajith Kumar, G.S.; Jayachandran, R.; Mathew, Jyothis; Radhakrishnan, E.K.
Abstract: Wide varieties of antibiotics are used in poultry farms to improve the growth and also to control the infection in broiler chicken. To identify the seriousness of the same in the poultry sector, current study has been designed to analyze the presence of tetracycline in poultry feed and also the tetracycline resistance among the bacteria released through the excreta of poultry. In the study, 27 bacteria belonging to the Escherichia coli and Klebsiella pneumoniae . were isolated from the faecal samples collected from five different farms. Antibiotic susceptibility analysis showed 77% of E. coli and 100% of the K . pneumoniae . to be resistant to tetracycline. Further, molecular screening for tetA and tetB genes showed 85.18% of isolates to have tet A and 22.22% with tet B. The presence of tetracycline in collected feed samples was also analysed quantitatively by Liquid chromatography-mass spectrometry (LC-MS). Here, three out of five feed samples were found to be positive for tetracycline. The study showed a direct correlation between the antibiotic supplemented feed and the emergence of antimicrobial resistance among the intestinal microflora. The results of the study indicate the need for strict control over antibiotic use in animal feed to limit the rapid evolution and spread of antimicrobial resistance. Highlights: Tetracycline antibiotics were detected in poultry feeds. Tetracycline resistant bacteria were isolated from the faeces of the commercial broilers. tet A and tet B genes were detected from the resistant bacterial isolates.